Physicochemical, Microbiological, and Sensory Properties of Probiotic Drink Made from Wild Horse Milk with Modified Banana Flour Addition - Agustin, Arin Tria; Sulaeman, Ahmad; Setiawan, Budi (Faculty of Animal Science, Universitas Brawijaya, 2023)
Dairy products from wild horses in Sumbawa Island, Indonesia, are promising to be developed as a probiotic source due to naturally occurring lactic acid bacteria. However, it is less favored due to its pronounced horse flavor. The development of products can beaccomplished by converting them into a probiotic drink and blending them with other ingredients to create a product with enhanced nutritional and sensory characteristics. This research aims to formulate probiotic drinks by blending wild horse milk and modified banana flour (MBF), evaluating their physicochemical and microbiological attributes and sensory quality. A one-factor, Completely Randomized Design (CRD) experimental design was employed in this research. The treatment involved the addition of MBF at three specific concentrations: 0%, 5%, and 10%. The results revealed that the addition of MBF led to significant differences (p<0.05) in the physicochemical properties (pH, viscosity, total dissolved solids, and syneresis). All formulations exceeded the minimum Lactic Acid Bacteria (LAB) requirements set by the Indonesian National Standard (SNI) 2981:2009, ranging from 1.57x109 to 2.35x109 CFU.mL-1. According to the sensory evaluation, probiotic drinks containing 5% MBF exhibited the highest sensory quality, stimulating appetite with dominant attributes such as a brownish-white color, sour taste, minimal skunky flavor, and a slightly sandy/coarse fiber texture. In conclusion, adding MBF enhanced the probiotic drinks' physicochemical properties, total LAB content, and sensory quality